2017
DOI: 10.1214/15-aop1040
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation and high disorder

Abstract: Given a field {B(x)} x∈Z d of independent standard Brownian motions, indexed by Z d , the generator of a suitable Markov process on Z d , G, and sufficiently nice function σ : [0, ∞) → [0, ∞), we consider the influence of the parameter λ on the behavior of the system,We show that for any λ > 0 in dimensions one and two the total mass x∈Z d u t (x) → 0 as t → ∞ while for dimensions greater than two there is a phase transition point λ c ∈ (0, ∞) such that for λ > λ c , Z d u t (x) → 0 as t → ∞ while for λ < λ c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…One may see a similar result in our earlier paper [16] where we consider a stochastic heat equation driven by space-time white noise on the one-dimensional torus R/Z rather than on R. Because R is not compact, we need to make significant modifications to the method of [16] especially when we estimate moments; see §3.1. Once we are able to prove that sup x∈R v(t , x) can be controlled by v(t) L 1 (R) , we appeal to a known result about dissipation of the total mass of the solution (see Chen, Cranston, Khoshnevisan, and Kim [4]) to prove Theorem 1.2; this is done in §4. Finally, we combine the results from § §2-4 in order to verify Theorem 1.1 in §5.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…One may see a similar result in our earlier paper [16] where we consider a stochastic heat equation driven by space-time white noise on the one-dimensional torus R/Z rather than on R. Because R is not compact, we need to make significant modifications to the method of [16] especially when we estimate moments; see §3.1. Once we are able to prove that sup x∈R v(t , x) can be controlled by v(t) L 1 (R) , we appeal to a known result about dissipation of the total mass of the solution (see Chen, Cranston, Khoshnevisan, and Kim [4]) to prove Theorem 1.2; this is done in §4. Finally, we combine the results from § §2-4 in order to verify Theorem 1.1 in §5.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…These distinctive features of the peaks and valleys in PAM are expected to be present in the case of parabolic Anderson equation. In fact, [CCKK17] showed that if the initial data decays at infinity faster than the Gaussian kernel, then the total mass of the solution of the parabolic Anderson equation dissipates, that is, it vanishes sub-exponentially as t → ∞. When (1.1) is considered on the torus instead of R, [KKMS20] proved among other things that the supremum of the solution is localized in space.…”
Section: Introductionmentioning
confidence: 99%
“…For Eq. (1.1a) in the whole space, the weak intermittency of the solution both on the real line ( [17]) and on the lattice ( [9,18,20]) has been studied. For the continuous Eq.…”
Section: Introductionmentioning
confidence: 99%